Efficacy and safety of endoscopic intraperitoneal subserosal dissection for gastric submucosal tumors with extraluminal growth pattern - Ma, Li-Yun; Guo, Ke-Yi; Liu, Xin-Yang; He, Meng-Jiang; Chen, Wei-Feng; Lin, Sheng-Li; Gong, Yao-Yao; Zhou, Ping-Hong; Hu, Jian-Wei (Endoscopy, 2025)
Endoscopic intraperitoneal subserosal dissection (EISD) has been reported to be a promising modified tunneling technique for gastric submucosal tumors (SMTs) with a predominantly extraluminal growth pattern. We evaluated the safety and efficacy of EISD for gastric extraluminal SMTs.We prospectively enrolled consecutive patients who underwent EISD for gastric extraluminal SMTs between October 2018 and March 2024. Clinicopathological characteristics and procedure-related parameters were analyzed.10 patients with 11 gastric extraluminal SMTs were included. The mean (SD) longest and shortest specimen diameters were 2.1 (0.9) cm (range 0.5–4.0) and 1.8 (0.7) cm (range 0.4–3.0), respectively. All SMTs (100%) were resected en bloc, and 10 (90.9%) were retrieved en bloc. The mean (SD) resection and suture times were 58.9 (31.5) minutes (range 26–125) and 12.4 (10.1) minutes (range 3–25), respectively. Two patients experienced type I mucosal injury at the tumor site, and no major adverse events occurred. The mean postoperative hospital stay was 3.4 (SD 0.8) days (range 3–5). No recurrence or metastasis occurred during a mean follow-up period of 32.1 (SD 18.8) months (range 7–71).EISD appeared to be a feasible and safe method for removing gastric extraluminal SMTs in selected patients.